KONTRIBUSI CARA BELAJAR TERHADAP HASIL BELAJAR MATA DIKLAT STATIKA BANGUNAN SISWA KELAS XI TEKNIK BANGUNAN SMK NEGERI 1 TANJUNG RAYA - 414-419 , Ruly Syari (Universitas Negeri Padang, 2014)
ABSTRACT This research is purposed to find out the level of contribution of learning method to the learning result of Building Static subject of Class XI Building Engineering students at SMKNegeri 1 Tanjung Raya. Data were collected by using questionnaire and documentation of student’s grades, and were processed by using correlational analysis technique. Correlation test provided r 0.826 ≥ r 0.288, so that the proposed hypothesis is accepted. Determinant coefficient formula was aplied in finding the level of contribution of variable X of variable Y, and the result 68.23%. Based on this research, it can be concluded that the learning method has a contribution to the learning result of Building Static subject of Class XI Building Engineering students at SMKNegeri 1 Tanjung Raya as much as 68.23% and the rest of 31.77% is expected from other factors. Keywords: Learning method, learning result.